Mechanisms of fluoroquinolone resistance among Escherichia coli isolates from urinary tract infections in Thailand - Nipaporn Tewawong; Siriporn Kowaboot; Warangkana Lektrakul; Utsanee Supcharoengoon; Naiyana Watanagul; Pannamthip Pitaksajjakul (PLoS ONE, 2025)
Escherichia coli is the major causative agent for urinary tract infections (UTIs), and fluoroquinolones (FQ) are commonly used in the treatment of patients with UTIs. The surge in FQ-resistant E. coli is an important public health threat worldwide. We investigated the prevalence and mechanisms of FQ resistance among FQ-resistant E. coli isolated from UTI patients. A total of 131 FQ-resistant E. coli strains were characterized and broth microdilution assay showed that 108 strains (82.4%) were highly resistant to ciprofloxacin (MIC ≥ 32 μg/mL). All strains were analyzed for plasmid-mediated quinolone resistance (PMQR) genes, with 37 (28.2%) testing positive. Among the PMQR genes detected, aac(6’)-Ib-cr was the most frequent, found in 30 strains (22.9%), followed by qnrS in 10 strains (7.6%) and qnrB in 1 strain (0.8%). PCR assay showed that all carried acrA, acrB, and tolC genes, but 33 strains (25.2%) revealed at least 4-fold reduction in ciprofloxacin MIC when using PAβN and CCCP as efflux pump inhibitors, indicating the role of the AcrAB efflux pump in ciprofloxacin resistance in these strains. The 19 strains of high-level ciprofloxacin-resistant E. coli were selected to determine the target enzyme alteration by PCR assay and DNA sequencing. Genetic analysis revealed that 16 strains (84.2%) had double mutations in gyrA (S83L and D87 to N or Y) with single mutation in parC (S80I), while 3 strains (15.8%) had double mutations in gyrA (S83L and D87 to N or Y) and parC (S80I and E84 to G or V). The positive efflux activity was linked to increased MIC values of ciprofloxacin (P < 0.001). Overall, the carriage of PMQR genes, efflux activity, and target mutations across E. coli strains contribute to ciprofloxacin resistance, a result that may necessitate a reassessment of the antibiotics in use for empirical UTIs therapy.